The Relationship Between Self-Efficacy and Self-Care Management in Hypertension Patients in the Neglasari Community Health Center, Tangerang City - Dede Rifaldi Dede Rifaldi; Lindawati (Journal of Noncommunicable Diseases Prevention and Control, 2025)
Background: Hypertension is a chronic disease that can be controlled with self-care management to prevent complications. There are several factors that affect it, one of which is self-efficacy. This is needed for hypertension sufferers to improve their health through confidence in carrying out self-care management. Hypertension is a dangerous cardiovascular disorder including risk factors for hypertension, organ damage, physiological abnormalities, and abnormalities of the cardiovascular system. Research Objective: To determine the relationship between self-efficacy and self-care management in hypertensive patients in the area of the Neglasari Health Center, Tangerang City. Research Method: The method used in this study is cross sectional. The sampling method in this study is purposive sampling. The sample used in this study was 84 respondents. The instrument used in this study is a demographic data questionnaire, self-efficacy questionnaire and self-care management questionnaire. Research Results: The results of the Chi Square test obtained a P value of 0.004 smaller than the significant value (α=0.05). Conclusion: The results of this study show that there is a relationship between self-efficacy and self-care management in hypertensive patients.